2004
DOI: 10.2337/diabetes.53.2007.s152
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Effects on Pancreatic β-Cell Gene Expression and Function

Abstract: The hormone leptin is secreted from white adipocytes, and serum levels of leptin correlate with adipose tissue mass. Leptin was first described to act on the satiety center in the hypothalamus through specific receptors (leptin receptor [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
193
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(205 citation statements)
references
References 82 publications
8
193
1
3
Order By: Relevance
“…During fetal life, insulin is one of the major growth factors and it has been shown that leptin inhibits insulin release in pancreatic b-cells. 6,8 A possible peripheral effect of leptin during fetal development is further supported by the observation that functional leptin receptors are already expressed in pancreatic islets of fetal rats. 47 Studying the relation between the LEPR SNPs and umbilical cord insulin levels might support the proposed mechanism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…During fetal life, insulin is one of the major growth factors and it has been shown that leptin inhibits insulin release in pancreatic b-cells. 6,8 A possible peripheral effect of leptin during fetal development is further supported by the observation that functional leptin receptors are already expressed in pancreatic islets of fetal rats. 47 Studying the relation between the LEPR SNPs and umbilical cord insulin levels might support the proposed mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…The hormone and its receptor are also expressed in other tissues, including pancreatic b-cells where it inhibits insulin secretion. [7][8][9] During pregnancy, leptin is produced by maternal and fetal adipose tissue and also by the placenta, and in contrast to maternal leptin levels, umbilical cord leptin levels are positively correlated with birth weight. 10,11 The association between single nucleotide polymorphisms (SNPs) in the leptin (LEP)/leptin receptor (LEPR) gene and birth weight has not been studied, this in contrast to the large number of (inconclusive) studies on the association with type 2 diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PPAR- is a transcription factor preferentially expressed in adipose tissue [37] and it is known that its activation, as we have observed in adipocytes exposed to hyperoxia, could improve insulin resistance [46]. HIF-1 leptin are important regulators of hundreds of target genes involved in several biological functions, such as cellular metabolism, cell growth and apoptosis and restoration of the oxygen supply [44,45]; nevertheless, their expression was not modified by hyperoxia. Finally, ANGPTL4 is a gene involved in glucose and lipid metabolism, mainly involved in the regulation of plasma triacylglycerides metabolism by inhibition of LPL [35].…”
Section: Discussionmentioning
confidence: 75%
“…The effect of elevated leptin levels on the so-called 'adipoinsular axis' may also provide another potential mechanism for the impaired insulin secretion in Alox5 −/− mice. For example, since leptin has been shown to inhibit insulin biosynthesis and secretion [35,36], the increased plasma leptin in Alox5 −/− mice could also decrease insulin production and secretion from beta cells, in addition to what is directly affected by 5-LO itself. This could be particularly relevant in older mice in which adiposity has substantially increased.…”
Section: Discussionmentioning
confidence: 99%